S14.1 Sexual contact networks, STI transmission and the effectiveness of interventions: insights from mathematical modelling. (14th July 2019) - Althaus, Christian
Abstract : University of Bern, Institute of Social and Preventive Medicine, Bern, Switzerland Sexual contact networks are a key determinant for the spread of sexually transmitted infections (STIs). The impact of different sexual contact structures on the effectiveness of interventions is not always well understood. Mathematical modelling provides an excellent tool to study the interrelationship between sexual contact networks, STI transmission and intervention effectiveness. We use deterministic, population-based as well as stochastic, individual-based transmission models to study the effects of control interventions against Chlamydia trachomatis and Neisseria gonorrhoeae . We illustrate that an accurate description of heterosexual contact networks is critical to evaluate the effectiveness of screening and partner notification strategies against chlamydia. We further analyse antibiotic resistance surveillance data to estimate the rates at which antibiotic-resistant N. gonorrhoeae spread in heterosexual men (HetM) and men who have sex with men (MSM). Interestingly, we can show that antibiotic-resistant N. gonorrhoeae spread faster with more treatment, not more sexual partners. The effectiveness of control interventions for an STI strongly depend on the life history of the disease and the underlying sexual contact structure. Disclosure: No significant relationships.